Microsurgical anatomy of the lateral walls of the pituitary fossa - (:unkn) unknown (SPRINGER WIEN, 2005)
Background. The aim was to evaluate the microanatomy of the lateral wall of the pituitary fossa in cadavers. Methods. Histological sections of sellar-parasellar specimens from 13 cadaver heads were examined. The thickness of the pituitary capsule and inferior and lateral walls of the pituitary fossa were measured, and the collagenous structure of these layers was evaluated. Findings. The pituitary gland is enveloped by a tough, thin, fibrous capsule. The inferior wall of the pituitary fossa is composed of relatively thick dura (mean thickness in the 13 specimens, 171 mu m). Each lateral wall of the fossa has a thin layer of dura (mean thickness in the specimens, 85 mu m). The pituitary capsule and the dural layers in the lateral and inferior walls of the fossa were immunopositive for collagen types I and II. Collagen types III, IV and V were detected only in the pituitary capsule. Conclusions. Weakness of the lateral walls of the pituitary fossa and the degree to which collagen fibres in the pituitary capsule have been biochemically damaged are important factors in infiltration of the cavernous sinus by a pituitary adenoma.
Keywords: anatomy; cavernous sinus; collagen; pituitary adenoma; pituitary gland; sella; CAVERNOUS SINUS INVASION; SELLAR COMPARTMENT; MEDIAL WALL; ADENOMAS; INVOLVEMENT; CAPSULE; TUMORS